INNOVATION MANAGERS FOR THE COUNTRY’S TECHNOLOGICAL SOVEREIGNTY - L. D. Gitelman; A. P. Isaev; M. V. Kozhevnikov; T. B. Gavrilova (Стратегические решения и риск-менеджмент)
The article substantiates the authors’ position, supported by empirical data, on the sharp increase in the intellectual intensity of managerial activities and on the transformation of the managerial profession into one of the most complex, gaining particular importance in the organisation of the innovation process for technological sovereignty. The increasing role of management science in understanding the ongoing turbulent changes, developing methodologies for proactive management and identifying competencies in demand in the economy is highlighted. The need for the introduction of advanced learning in these conditions is demostrated; the authors’ experience in its development and implementation in terms of specific organisational models, content and teaching methods is presented. Within the framework of the proposed concept of further education, it is necessary to introduce a management specialisation focused on specific industries into the existing system of higher education. It will provide enhanced fundamental and applied training, a significant increase in the volume of practice and will enable students to master the engineering-economic and engineering-managerial knowledge necessary for taking into account interdisciplinary relationships between high technology, economics and finance when making management decisions.